Empirical evidence of the role of Ecosystem-Based Management in qualifying Marine Environmental Impact Assessment - Andrade, Mariana Martins de (2018)
Externalities caused by human transformations in ecosystems structure and functioning has been threatening environmental quality and social welfare in all socioecological systems, including coastal zones. Environmental Impact Assessment (EIA) is an instrument widely used to evaluate the feasibility of developments and projects that can potentially provoke changes in biophysical-human environment. However, EIA generic and fragmented approach has not properly been considering people and environmental particularities, such processes and benefits to society, in decision making. Ecosystem-Based Management recently emerged as a strategy that can qualify EIA, by embracing ecosystem processes and services (ES), human dimensions, social engagement and Local, Traditional and Scientific Ecological Knowledge. Using a case study of a contested Port expansion in São Sebastião, São Paulo, Brazil, that endangered the sustainability of an adjacent bay (Araçá Bay), we selected analytical categories comprising different stakeholders, ecosystem services and disturbances scenarios to understand the role of EBM in coastal EIA. We presumed that stakeholders with deeper relationships with the place could provide more comprehensive assessments about changes in the availability of main local ES, as a result of greater sense of place, access to different sources of knowledge and opportunities to social participation. Also, an EBM approach would provide a more robust, i.e., a wider and more integrated assessment of impacts in the provision of the ES than the Environmental Impact Study (EIS) of the port expansion. We performed in-depth interviews with four different groups of stakeholders and analyzed their speeches with discourse analysis and statistical inquiries to assess ES scores of occurrences in current (Two-way ANOVA) and disturbances scenarios (Repeated measures ANOVA and PERMANOVA), besides their main argumentation patterns. We compared these results with the port expansion EIS to assert to robustness of the method. The groups had different perceptions from each other, which depended on the scenario and ES evaluated. We corroborated the hypotheses: groups\' closer, deeper and more engaged relationships with the place had more comprehensive assessments of changes in the ES; and stakeholders perceptions reflected trade-offs of the local urban conflicts, providing a higher variety and more integrated assessments of impacts than the Environmental Impact Study of the Port expansion. The diversity of forms of knowledge, behaviors and functions, in temporal and spatial scales, proved to be valuable for the groups\' assessments of resource and the territory, and the choice of the analytical categories was fundamental to consolidate the understanding of local socioecological processes. We concluded that the method tested was efficient and respected the intrinsic variability of coastal zones and its function as a socioecological system to assert that EBM has a great potential to improve the effectiveness of EIA.